The Herd Boy and His Hermit - Yonge, Charlotte M. (Charlotte Mary), 1823-1901 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Herd Boy and His Hermit" by Charlotte M. Yonge is a novel published during the late 19th century. The story takes place in the backdrop of the Wars of the Roses and follows the adventures of Hal, a young shepherd boy, as he navigates relationships and societal challenges in a tumultuous historical period. The novel centers on Hal and his interactions with a young noble girl named Anne St. John, as well as the mysterious hermit and the implications of Hal$1 (Bs hidden lineage. At the start of the novel, the reader is introduced to Hal, lying on a grassy hill on the moors, longing for the stars while caring for his flock. The tranquility is disrupted when he hears the cries of a lost girl, Anne. Hal rescues her after she has fallen from her pony while hawking with her companions. Despite their differences in background and status, a bond begins to form between them. The opening sets up themes of innocence, friendship, and the contrasts between the simplicity of Hal's shepherd life and the complexities of Anne's noble lineage. It hints at larger issues such as identity and social class in a setting where the characters must navigate the dangers of a divided kingdom. As Hal's adventures intertwine with those of the hermit and Anne, the stage is set for a story rich with exploration of personal growth and the pursuit of knowledge amidst the chaos of their world. (This is an automatically generated summary.)s
Release date is 2004-03-01
Produced by Sandra Laythorpe and David Widger
Keywords: Clifford, Henry de Clifford, 14th lord, 1455?-1523 -- Fiction; Henry VI, King of England, 1421-1471 -- Fiction